Damage equivalent of the flexible pavement variation with load applied - Buhari, Rosnawati (Scientific.Net, 2013)
Previous research revealed that influence function is strongly influenced the appropriateness of pavement damage prediction and are demanding to be concern in order for better prediction of long term pavement performance. In order to identify the impact of traffic loading condition on the influence function of the pavement toward failure, further stucdy was done to determine the exponential value in the Damage Equivalent Law for varies loading condition and also vehicle speeds. To achieve the aims, the simple quarter truck model was efficiently used with personal computers to predict pavement loading. Towards reality of traffic loading condition will contain a distribution of axles load between unladen and fully laden, the study was further taking into account realistic axle load variation. Results are presented from a study to evaluate the relative influence of truck speed and axle load variation on the stiffness of the asphaltic layer and thus the primary response of the pavement. In conclusion, the exponential value in the Equivalent Damage Law is clearly sensitive to both factor.